Moody Attunement in Giorgio de Chirico's Metaphysical City. (1st March 2018) - Weston, Dagmar Motycka
Abstract : Overly pragmatic conceptions of the city pose a threat to the urban public realm. The Surrealist view offers an alternative. It is explored here by architectural theorist and historianDagmar Motycka Weston, Honorary Research Fellow at the University of Edinburgh, through the work of the Greek‐Italian artist Giorgio de Chirico, which posits other ways to conceive of cities – particularly in relation to the German Romantic notion of 'moody attunement' ( Stimmung ).